(untitled) (Global Journals of Research in Engineering, 2024)
The purpose of this article is to study the peculiarities of adaptation of cultural heritage buildings to modern urban space using the example of Tbilisi The issue is topical because the monuments of cultural heritage require preservation and harmonious coexistence with a modern city Today cultural heritage monuments are undergoing transformation Modern additions will create a connection between the past and the present turn them into public buildings and places of social relations The monument is no longer a museum exhibit it is undergoing evolutionary development along with the city However there are some risks The analysis of the buildings carried out in the city of Tbilisi revealed a variety of approaches to the protection of cultural heritage restoration - reconstruction conservation and new architecture in historical building-development This is caused by a number of factors Each building harmoniously fits into the modern urban space originally preserving the authentic appearance and balanced approach to new technologies and architectural forms form a continuous chain of connections from the past to the future ensure the sustainability preservation of historical value and reuse of the cultural heritage building The analysis revealed that the transformation of cultural heritage buildings requires a careful approach since it is associated with a number of legislative regulations restrictions as well as technical and structural problems Therefore it is important to analyze and evaluate the general condition of the building structure describe historical architectural details etc in accordance with generally accepted practice Thus the process of integrating an old building into a modern one requires the development of a clear plan to protect its historical integrity and sustainability Public involvement and awareness are important factors for the successful renovation of cultural heritage monuments The dialogue with the citizens ensures the strengthening of the role of the historicity of the building in the modern urban space